Evaluation of the physical, chemical, bacteriological and trace metals concentrations in different brands of packaged drinking water - Jagaba A.H.; Kutty S.R.M.; Hayder G.; Onsa Elsadig E.H.; Lawal I.M.; Sayed K.; Abubakar S.; Hassan I.; Umaru I.; Zubairu I.; Nasara M.A.; Soja U.B. (International Association of Engineers, 2023)
Biochemical oxygen demand; Dissolved oxygen; Fluorine compounds; Groundwater; Potassium chloride; Trace elements; Turbidity; Water absorption; Water quality; 'current; Analytical procedure; Food and Drug Administration; Human survival; Packaged water; Physio-chemical; Potable water quality; Total bacterial count; Trace metal; Trace metal concentration; Potable water